MEMAHAMI MAKNA DERAJAT LAKI-LAKI LEBIH TINGGI ATAS PEREMPUAN DALAM SURAT AL-BAQARAH/2: 228 - Nelli, Jumni (Marwah: Jurnal Perempuan, Agama dan Gender, 2014)
Statements are often heard that men of higher social status of women has been received and considered true. This seems to have sealur with the letter al-Baqarah / 2: 228, âthe husband has a degree on the wife.â It is interesting to study whether it is Allah His discriminate because of differences in sex and then certainly not in line with the other verses stated that âthe most noble in the sight of Allah is the most piousâ,. It turns out that the word darajah in paragraph 228 surat al-Baqarah this does not mean kemulyaan, pronunciation darajah / excess is able to drop the divorce and ruju â. Excess in the right divorce because her husband can drop the divorce against his wife with himself, in contrast with the wife who require a third party to divorce her husband, as a judge. Excess in ruju âthe husband is entitled to received rujÃ»â his goodwill towards his wife who was in rajâÃ® divorce status, while his wife was pregnant. In addition, remember that the wife has the right to be met by her husband in the form of liability protection and living physically and spiritually